Climate+ = Rice Crop Manager Advisory Service (RCMAS) + Agro-climatic Advisory Portal (ACAP) - Castillo, Rowena; Balanza, Jane Girly; Baradas, Airene Claire; Vila, Jerome; Collado, Wilfredo; Tamani, Luis Alejandre; Alvina, Lorenzo; Wei, Xiaojing; Hellin, Jon (International Rice Research Institute, 2024)
The presentation provides the overview of the Climate+, the initial results of the pilot study in Bicol Region and the next steps to refine the functionality of Climate+ with sub-seasonal flood early warning model. It also outlines the outputs of the Climate+ write shop that includes capacity needs or requirements for other Regions to adopt Climate+, identified other potential stakeholders and policy instruments for scaling, suggestions to improve decision logic, and potential roles and interactions among the identified partners. This was presented during the ClimBeR workshop with its partners and stakeholders from non-government and government organizations held on September 25-26, 2024.